THE ROLE OF SOCIAL ENTERPRISE IN YOUTH DEVELOPMENT: EMPIRICAL EVIDENCE FROM KASHMIR - Dr Bilal Ahmad Dar , Dr Shafiqa Gul (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
There is very little data on youths as a framework for theorizing, notwithstanding the emerging research on social entrepreneurship throughout recent times. This paper explores, from the optimistic lens of youth development, the impact of social entrepreneurship on youth development. It discusses how the involvement of young people in social entrepreneurship helps to improve their sense of meaning and purpose. Using evidence through semi-structured interactions with 150 young people with observation methods, this paper showed that social entrepreneurship helps in the growth of youth by promoting social understanding, positive social communication, skill and power. This research paper illustrates current guidance for the future of J&K social entrepreneurship. Together with a total population of 13.6 million, J&K faces structural youth excess. The findings of this study indicate that the need to improve youth management knowledge by applying them with appropriate education as well as career education. It will bring an improvement in the participants' social standing and gradually raise the living conditions of the populace. It is a powerful labour push state via an annual growth in the trained youth force of 6 per cent. By embracing social entrepreneurship to enhance wellness, education, business & other related disciplines,